ANALISIS STRATEGI PENGEMBANGAN WISATA KOTA DI KOTA MALANG - Muhammad Danang Setioko (Jurnal Pariwisata Pesona, 2019)
In order to build a region is need a control in many sector. One of the most sector which can be a priority to rebuild the region is tourism which is growing right now. For the malang city's own number 3,376,722 foreign tourists and 8.754 domestic tourists in 2015, but unfortunately only a few are enjoying the tourist destinations of Malang town. Most prefer to travel to the Batu city and artificial in nature in Mount Bromo whereas in Malang town just as a haven and a meal for later traveled to other regions.In connection with this we need a proper analysis to determine the strengths, weaknesses, threats and opportunities that exist in the tourism city of Malang. So the authors chose to use SWOT analysis here because using SWOT analysis can be described with good conditions and the condition of the exsisting development of tourism in Malang today. Therefore, here I need a key informant which may provide information with respect thereto.The results of this study indicate that the strategy of development of tourism destinations more directed to the Malang town developments such as city tours MICE activities, culinary, educational and shopping that indeed is the hallmark of the city tour.